MENINGKATKAN KETERAMPILAN MEMOTONG KUKU MELALUI METODE DEMONSTRASI BAGI ANAK TUNAGRAHITA RINGAN - Yusfidarwati - - (Jurnal Penelitian Pendidikan Khusus, 2012)
This research aim to to increase cross cut skill  of nail to child of Tunagrahita Light through method demonstrate in Study of Education Help Ownself ( PMDS), at class student of III  SLB.C  Town of Payakumbuh. This research in form of research of Action Class that goes to during two cycle. Each  consist of cycle of  I  , five times meeting, cycle of II four times meeting. Result of research is the happening of cross cut  improving  of skill  of child nail of Tunagrahita Light without in assisting others. Through demonstration method can improve  skill to cut child nail of Tunagrahita Light.